Aplikasi Teknologi Penginderaan Jauh Untuk Pengkajian Sumber daya Wilayah Pesisir Di Kepulauan Seribu, Jakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Studi S1 Gizi Kesehatan Fak. Kedokteran UGM, 2006)
Coastal area in Seribu archipelago is a potential area, but it is also an vulnerability area from the damage caused by natural processes and human activities. Main function of Seribu archipelago are as natural conservation, fisheries, and recreation and should be managed integrately. This process needs the availability of natural resources data in coastal area which can be derived from remote sensing image. This research explores the use of remote sensing technology for detecting and mapping of natural resources of coastal in Seribu archipelago, Jakarta. The natural resources in coastal which can be derived from satellite image are: coastal line, crude bathimetric mapping, land cover mapping, and coral reef condition and distribution. If all information can be identified and mapped integrately, planning of use and conservation can be well arranged. The research shows, image of Landsat 7 ETM+ can be use to derived of information related to coastal, i.e.: temporary coastal line, crude bathimetric mapping, land cover mapping in the coastal, and coral reef condition and distribution. Visual interpretation shows the results agree with information on Indonesian LPI Map in scale of 1: 50.000.